Treatment of Genetic Forms of Nephrotic Syndrome - Kemper, Markus J.; Lemke, Anja (Frontiers in Pediatrics, 2018)
Idiopathic steroid-resistant nephrotic syndrome (SRNS) is most frequently characterized by focal segmental glomerulosclerosis (FSGS) but also other histological lesions, such as diffuse mesangial sclerosis (DMS). In the past 2 decades a multitude of genetic causes of SRNS have been discovered raising the question of effective treatment in this cohort. Although no controlled studies are available, this review will discuss treatment options including pharmacologic interventions aiming at the attenuation of proteinuria in genetic causes of SRNS, such as inhibitors of the renin-angiotensin-aldosterone system (RAAS) and indomethacin.. Also the potential impact of other interventions to improve podocyte stability will be addressed. In this respect the treatment with cyclosporine A (CsA) is of interest, since a podocyte stabilizing effect has been demonstrated in various experimental models. Although clinical response to CSA in children with genetic forms of SRNS is inferior to sporadic SRNS some recent studies show, that partial and even complete response can be achieved even in individual patients inherited forms of nephritic syndrome. Ideally, improved pharmacologic and molecular approaches to induce partial or even complete remission will be available in the future thus slowing or even preventing the progression towards end-stage renal disease.